Remote learning engagement and learning outcomes during school closures in Ghana. (2022) - Wolf, Sharon; Aurino, Elisabetta; Suntheimer, Noelle M.; Avornyo, Esinam A.; Tsinigo, Edward; Jordan, Jasmine; Samanhiya, Solomon; Lawrence Aber, J.; Behrman, Jere R.
Highlights: Leverages a longitudinal study in peri‑urban Ghana to examine learning during school closures. Documents inequalities in access to quality remote learning opportunities. Documents persistent learning gaps between vulnerable and non-vulnerable groups. Abstract: Remote learning programs were rapidly implemented throughout the COVID-19 pandemic during school closures. We drew on an ongoing longitudinal study of a cohort of children in the Greater Accra Region of Ghana to survey children ( N = 1, 844), their caregivers, and teachers to examine learning experiences during the ten months of school closures in Ghana in 2020. We documented inequalities in remote learning opportunities offered by public and private schools, as well as who accessed remote learning and the quality of learning opportunities. In addition, controlling for pre-pandemic learning outcomes, we documented learning gaps, with food insecure, low socioeconomic status, and public-school children performing significantly worse than their peers (0.2–0.3 SD gap). Results highlight pandemic-related inequalities in a cohort of Ghanaian primary schoolchildren.